2018
DOI: 10.1371/journal.pone.0199923
|View full text |Cite
|
Sign up to set email alerts
|

From welcome culture to welcome limits? Uncovering preference changes over time for sheltering refugees in Germany

Abstract: Europe recently experienced a large influx of refugees, spurring much public debate about the admission and integration of refugees and migrants into society. Previous research based on cross-sectional data found that European citizens generally favour asylum seekers with high employability, severe vulnerabilities, and Christians over Muslims. These preferences and attitudes were found to be homogeneous across countries and socio-demographic groups. Here, we do not study the general acceptance of asylum seeker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 24 publications
5
29
0
2
Order By: Relevance
“…It also reviews the existing literature on migration (economic or forced) and housing markets. 3 A repeated choice experiment by Liebe et al (2018) provides evidence which is consistent with this reading of our results. Investigating the attitudes of Germans towards refugee accommodations in their neighborhoods, the study finds that the majority of Germans rather disapprove of refugee housing in proximity of their neighborhoods and that this view has not changed over the twelve months since November 2015, i.e.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…It also reviews the existing literature on migration (economic or forced) and housing markets. 3 A repeated choice experiment by Liebe et al (2018) provides evidence which is consistent with this reading of our results. Investigating the attitudes of Germans towards refugee accommodations in their neighborhoods, the study finds that the majority of Germans rather disapprove of refugee housing in proximity of their neighborhoods and that this view has not changed over the twelve months since November 2015, i.e.…”
Section: Introductionsupporting
confidence: 87%
“…The study also found that about one fifth of the surveyed population which had formerly rather approved of the establishment of refugee accommodations in their vicinity no longer did so in 2016. According to Liebe et al (2018), this change in attitude may, at least in part, be attributable to growth in 'not in my backyard' (NIMBY) perceptions (Dear, 1992) among the surveyed population.…”
Section: Introductionmentioning
confidence: 99%
“…By focusing on Middle Eastern Muslim refugees, we can also contribute to a better understanding of prejudiced perception toward a so-far underrepresented but highly relevant group of targets. Whereas public debates about refugees are ubiquitious and controversial (Chouliaraki & Zaborowski, 2017;Czymara & Schmidt-Catran, 2017;Hager & Veit, 2019;Jäckle & König, 2017;Liebe, Meyerhoff, Kroesen, Chorus, & Glenk, 2018), the current scientifc understanding of refugee perception is limited (Bansak, Hainmueller, & Hangartner, 2016;Kotzur, Forsbach, & Wagner, 2017;Kotzur, Friehs, Asbrock, & Zalk, 2019).…”
Section: Targets' and Perceivers' Individual Characteristics Than By mentioning
confidence: 99%
“…An increasing number of Germans consider refugees to be a threat to German culture and to be responsible for increasing crime. 24 This is combined with antiimmigrant, anti-Muslim and anti-European stances, which has become more prominent on the back of the refugee crisis. 24 Alongside this, the scale of numbers of asylum seekers has required tremendous resources from the government in terms of: social integration, integration into the labour market, health and education.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…24 This is combined with antiimmigrant, anti-Muslim and anti-European stances, which has become more prominent on the back of the refugee crisis. 24 Alongside this, the scale of numbers of asylum seekers has required tremendous resources from the government in terms of: social integration, integration into the labour market, health and education. In 2015, social welfare payments amounted to 5.3 billion euros (169% more than in 2014) and in 2016, the figure was 21.7 billion euros for refugee-associated expenditure.…”
Section: Bmj Global Healthmentioning
confidence: 99%